Patient survival and kidney transplantation in different dialysis modalities under PD First Policy Thailand - Pornpen Sangthawan; Thammasin Ingviya; Songyos Rajborirug; Jirayut Janma; Siribha Changsirikulchai (PLoS ONE, 2025)
Background Thailand implemented a peritoneal dialysis (PD)-first policy under its universal health coverage (UHC) from 2008 to 2022. This study aims to describe patient survival during dialysis and after kidney transplantation (KT), and to identify factors associated with survival in these periods among UHC-covered patients undergoing PD, hemodialysis (HD), or transitioning between dialysis modalities. Methods This retrospective study analyzed data from patients receiving PD, HD, or KT, recorded by the National Health Security Office (NHSO) between January 2013 and December 2021. Patients were categorized into four groups: PD, HD, PD-to-HD transition, and HD-to- PD transition. Survival factors were analyzed using Cox proportional hazards models. Results Among 81,572 patients receiving kidney replacement therapy, 38.9% were on PD, 35.3% were on HD, 10.2% transitioned from PD to HD, and 15.6% transitioned from HD to PD. Patients transitioning from PD to HD had superior 3- and 5-year survival rates compared to the other three groups. Survival outcomes were significantly influenced by age at dialysis initiation, diabetes, and comorbidities. Overall, 1,517 patients (1.9%) received KT: 70.4% had PD, 19.8% HD, and 9.8% had transitioned. Median follow-up time before KT was 94.5 months. Post-KT survival rates were comparable across dialysis groups. Factors associated with post-KT survival were age, cardiac disease, antibody-mediated rejection, and delayed graft function. Conclusions Under Thailand’s PD-first policy, starting with PD and later switching to HD was linked to better survival than staying on a single modality or switching from HD to PD. A higher proportion of PD patients underwent KT compared to HD patients. Post-KT survival rates remained similar across all dialysis modalities. These findings underscore the importance of individualized dialysis modality selection and proactive transition planning to optimize patient outcomes.